Motivational strategies on volunteering intention among university students. - Ramdzan Ali, Al Amirul Eimer; Abd Hamid, Mohd Azrul Azlen (Human Resource Management Academic Research Society, 2020)
The concept of volunteering is more than just spending one’s time in activities that bring benefit to others. Volunteering has a greater impact on society at a larger scale. University’s students who actively involved in volunteering activities are of great help to the community as they will have a better chance in learning new opportunities and building new networking people from the industry. This paper aims to investigate the motivational strategies namely intrinsic and extrinsic motivation on volunteering intention among university students. The concept of religiosity is introduced as part of the motivational strategies as it is proven to be one of the students’ motivational factor to volunteer.